Analysis Of The Implementation Of Internal Control System On Non Performing Loan (A Case Study On Bank Bjb Kcp Cicurug) - Hidayat, Imam Riyadi; Nugroho, Gatot Wahyu; Indrawan, Andri (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to determine the implementation of internal control systems on credit delinquency in Bank BJB KCP Cicurug. The variable used in this research is the internal control system. This research is a qualitative study using a qualitative descriptive method, where data is collected from the research object and the internal control system in Bank BJB KCP Cicurug is analyzed. The data collection methods used in this research are interviews, observations, and literature review. The results of the research show that Bank BJB KCP Cicurug has implemented a comprehensive internal control system in managing credit risks. The credit granting process is conducted through strict evaluation stages, including credit feasibility analysis and financial assessment. Credit monitoring and supervision are carried out continuously to identify potential credit delinquencies and take appropriate actions. Bank BJB KCP Cicurug also has accurate and transparent accounts receivable recording procedures and a professional debt collection team. Additionally, the bank has a careful bad debt provisioning policy to manage problematic debts. Although the internal control system implemented by Bank BJB KCP Cicurug has significantly contributed to managing credit risks, the research also identified several challenges that need to be addressed.